Non-albicans Candida Vulvovaginitis: Treatment Experience at a Tertiary Care Vaginitis Center. Issue 1 (January 2016) - Powell, Anna M.; Gracely, Edward; Nyirjesy, Paul
Abstract : Objectives: The aims of this study are to analyze a cohort of women with vulvovaginal symptoms and positive cultures for non- albicans Candida (NAC) to determine whether yeast was responsible for their symptoms and to evaluate the mycological effectiveness of various regimens. Methods: This observational study was performed from retrospective chart review of patients with positive NAC cultures between April 1, 2008, and January 31, 2011, at a tertiary care vaginitis center. Patient intake demographics were entered into a database. Follow-up visits were analyzed for data about patient treatments and outcomes. Patients were considered a clinical cure if their symptoms were significantly improved and mycologic cure (MC) if later yeast cultures were negative. If clinical symptoms improved at the same time as MC, the isolate was considered the proximate cause for the symptoms. Results: One hundred eight patients meeting entry criteria were analyzed. Boric acid was effective at obtaining MC in 32 (78%) of 41 patients with C. glabrata, 3 of 3 patients with C. tropicalis, and 3 of 3 patients with C. lusitaniae . Fluconazole was effective as initial treatment for 3 (60%) of 5 patients with C. glabrata and 13 (81%) of 16 patients with C. parapsilosis . In 52.7% of C. glabrata, 66.7% of C. parapsilosis, and 57.1% of C. tropicalis cases, effective antifungal therapy led to symptom improvement. Conclusions: In a tertiary care vaginitis center, NAC, when isolated on culture, caused clinically significant infections in approximately half of symptomatic patients. A majority of infections can be effectively treated with boric acid or fluconazole regardless of the non- albicans Candida species. Abstract : In a tertiary care vaginitis center, non-albicans Candida yeasts caused clinically significant infections in approximately half of patients with these isolates.